Muslim Romance in Diaspora: Leila Aboulela’s “Minaret” (2005) and the Ethics of Reading in the West - Stotesbury, John A. (Armenian Folia Anglistika, 2009)
The inclination of theorizing literary works published in the Diaspora and in the post-colonial period, that has been observed recently tends to turn the investigation of the main components of literary works into a side task. Sudanese writer Leila Aboulela’s work can be considered one of the examples of such pieces of work. The novel is based on existential alternatives which are experienced by Sudanese women living with Muslim values in western society. The ambiguous norms in the Minaret by Aboulela are examined in the light of Andrew Gibson’s critical reception and receptivity.